The Effect of Perineal Wound Care Education on the Level of Knowledge and Compliance of Postpartum Mothers at Laiwui Community Health Center, South Halmahera - Isna Ariani Syam; Reny Retnaningsih (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Perineal wounds due to spontaneous tears or episiotomy are common conditions experienced by postpartum mothers and have the potential to cause complications if not properly cared for. Low knowledge and compliance of postpartum mothers in performing perineal wound care remains a problem in primary health care. This study aims to analyze the effect of perineal wound care education on the level of knowledge and compliance of postpartum mothers at the Laiwui Community Health Center, South Halmahera. The study used a quasi-experimental design with a one-group pretest–posttest approach. The study sample consisted of 40 postpartum mothers with perineal wounds and were selected using a total sampling technique. The intervention in the form of perineal wound care education was provided in a structured manner through counseling, leaflets, and live demonstrations. The level of knowledge and compliance was measured before and after the intervention using a standardized questionnaire. Data analysis was performed univariately and bivariately using the Wilcoxon Signed Rank Test. The results showed an increase in the level of knowledge and compliance of postpartum mothers after being provided with education. The Wilcoxon test showed a significant difference between knowledge levels before and after education (p < 0.05), as well as a significant difference in postpartum maternal compliance (p < 0.05). It can be concluded that perineal wound care education has a significant effect on increasing postpartum maternal knowledge and compliance. Structured and applicable education is recommended to be integrated as part of the standard postpartum care in primary health care to support maternal recovery and prevent postpartum complications.